A novel anti-OX40 human monoclonal antibody that blocks OX40/OX40L signaling and depletes OX40+ T cells - Zhen Li; Lin Liu; Xiaobo Chen; Yanqing Wang; Yuxuan Wang; Yuxiu Zhang; Bingqiang Zhang; Xiao Wu; Muhammad Omer Iqbal; Jin Chen; Yuchao Gu (Marine Life Science & Technology, 2025)
Tumor necrosis factor receptor superfamily member 4 (TNFRSF4), also known as OX40, plays a crucial role in the regulation of T-cell immune responses under normal physiological conditions. Abnormal expression of OX40 and its cognate ligand OX40L (TNFSF4) have been associated with various autoimmune diseases, indicating that blocking the OX40/OX40L pathway could be a promising strategy for the treatment of a broad range of T cell-mediated autoimmune diseases. Here, we screened and characterized a fully human anti-OX40 antibody (JY007) from a naïve human scFv phage library. JY007 has an affinity constant of 7.71 nmol/L and effectively inhibited the OX40-OX40L interaction at both molecular and cellular levels, with IC 50 values of 1.088 and 10.12 nmol/L, respectively. Furthermore, JY007 demonstrated the ability to deplete activated T lymphocytes through antibody-dependent cellular cytotoxicity (ADCC) activity, with an EC 50 of 5.592 pmol/L. The combination of ADCC and its antagonist activity against OX40 suggests potential efficacy in suppressing inflammatory responses mediated by the OX40/OX40L pathway. Additionally, we employed molecular docking, site-directed mutagenesis, and competitive ELISA to pinpoint the epitopes on OX40. The results revealed that JY007 binds to Pro 37 , Ser 38 , and Asp 40 of OX40. Interestingly, we also found that the most potent anti-OX40 antibody drug in the clinical stage, KHK4083, binds to different OX40 amino-acid residues, including Asp 74 , Lys 82 , Asp 117 , Ser 118 , Tyr 119 , and Lys 120 . This divergence suggests that the novel monoclonal antibody JY007 holds promise as a potential therapeutic option for patients with atopic dermatitis and may find broad applications in the treatment of autoimmune diseases.